Student´s key competencies required for applicability in practice – students' point of view - Vydrová, Janka (Univerzita Pardubice, 2018)
The competence of university students is a key issue. Due to the situation on the labour market, it is necessary to respond already in the university education of future young professionals. The aim of each educational institution is to have highquality graduates who are on the job market and able to adapt to the current situation. The aim of the paper is to identify a new approach in the education of young professionals based on identification of key competencies. In total, 586 questionnaires were evaluated. The research began in February 2017. The first phase was conducted through controlled interviews with 19 student groups. In total, there were 148 respondents in qualitative research. The quantitative research followed in April 2017 and ended in January 2018. The key competences identified were ranked according to their importance from the student’s point of view, and in the article the author dealt with those that the respondents identified as most important for the preparation of their next vocation. These are communication skills, knowledge of foreign languages, creativity, responsibility, teamwork, flexibility, punctuality and work under stress. Three research hypotheses have been identified. Hypotheses were verified using the Two-sample t-Test statistic for equal means.
Keywords: key competencies; universities; education; globalization; young professionals; self-education; self-reflection; J59; J89; M12; M20; M55